Reflections on the presentations from the rapid Health Impact Assessment perspective. (20th October 2021) - Green, Liz
Abstract: Liz Green is Consultant in Public Health, Policy and International Health / Programme Director for Health Impact Assessment at Public Health Wales. She co-authored a HIA report on the potential impacts from home and agile working on public health. https://whiasu.publichealthnetwork.cymru/en/hia-reports/